The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.jtho.2018.07.062
|View full text |Cite
|
Sign up to set email alerts
|

P23 Stage IIIb NSCLC and Curative Intention Treatment: Difficulties and Disparities in Brazil

Abstract: Background: Profiling of targetable oncogenic drivers has significantly improved outcomes in patients with nonesmall cell lung cancer (NSCLC). About 40% of individuals with metastatic lung adenocarcinomas may benefit from personalized treatment with kinase inhibitors. There is limited data of the distribution of oncogenic drivers other than ALK and EGFR in our region. In this study we performed next generation sequence (NGS) to study the distribution of molecular alterations in patients with advanced lung canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This could be attributed to the scarcity of thoracic oncology surgeons in the country 15 . Results from a retrospective cohort study in Brazil in patients with stage IIIB NSCLC showed that 30.4% of patients received cCRT and 8.7% patients received sCRT as part of initial therapy 24 . Another study (IIIA 20.9%, IIIB 22.4%) showed that only about one‐fourth of patients (24.6%) received curative surgery 25 that could be attributed to the unequal distribution of thoracic surgeons in the country 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be attributed to the scarcity of thoracic oncology surgeons in the country 15 . Results from a retrospective cohort study in Brazil in patients with stage IIIB NSCLC showed that 30.4% of patients received cCRT and 8.7% patients received sCRT as part of initial therapy 24 . Another study (IIIA 20.9%, IIIB 22.4%) showed that only about one‐fourth of patients (24.6%) received curative surgery 25 that could be attributed to the unequal distribution of thoracic surgeons in the country 26 .…”
Section: Discussionmentioning
confidence: 99%
“… 15 Results from a retrospective cohort study in Brazil in patients with stage IIIB NSCLC showed that 30.4% of patients received cCRT and 8.7% patients received sCRT as part of initial therapy. 24 Another study (IIIA 20.9%, IIIB 22.4%) showed that only about one‐fourth of patients (24.6%) received curative surgery 25 that could be attributed to the unequal distribution of thoracic surgeons in the country. 26 There is heterogeneity in the treatment pattern within Brazil 27 where although CRT is largely the SoC for treatment of patients with LA NSCLC, results of the retrospective analysis in elderly patients (>65 years) with unresectable LA disease has shown that about 40% of patients received best supportive care and about 30% of patients each received definitive radiotherapy alone or CRT.…”
Section: Discussionmentioning
confidence: 99%